2008
DOI: 10.1302/0301-620x.90b5.19803
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic bone cement

Abstract: Bone cements produced by different manufacturers vary in their mechanical properties and antibiotic elution characteristics. Small changes in the formulation of a bone cement, which may not be apparent to surgeons, can also affect these properties. The supplier of Palacos bone cement with added gentamicin changed in 2005. We carried out a study to examine the mechanical characteristics and antibiotic elution of Schering-Plough Palacos, Heraeus Palacos and Depuy CMW Smartset bone cements. Both Heraeus Palacos a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…There are some significant differences in the mechanical strength of different brands of bone cement, but these differences are small compared with other factors, such as temperature, fat, or blood in the cement [10]. In general, the mechanical strength used for definite fixation of prosthesis must have ultimate compression strength of more than 70MPa as described by international industrial standard [9, 43]. In our study, the compression strength of high dose ALBCs after elution does not exceed 70MPa in Lyo-Vancin and Strerile Vancomycin groups, regardless of the brands of PMMA used.…”
Section: Discussionmentioning
confidence: 99%
“…There are some significant differences in the mechanical strength of different brands of bone cement, but these differences are small compared with other factors, such as temperature, fat, or blood in the cement [10]. In general, the mechanical strength used for definite fixation of prosthesis must have ultimate compression strength of more than 70MPa as described by international industrial standard [9, 43]. In our study, the compression strength of high dose ALBCs after elution does not exceed 70MPa in Lyo-Vancin and Strerile Vancomycin groups, regardless of the brands of PMMA used.…”
Section: Discussionmentioning
confidence: 99%
“…(2008) performed an in vitro study comparing Palacos with gentamicin with the cements Palacos R + G and SmartSet GHV. All cements performed well, with minor differences.…”
Section: Discussionmentioning
confidence: 99%
“…This explanation was also suggested by an official statement from Heraeus Kulzer, given in Bridgens et al. (2008). Furthermore, a legal dispute between Heraeus Medical Nordic and Biomet at the Norwegian Complaints Board for Public Procurement regarding the procurement of cement has indicated that the suppliers of antibiotics and monomers, and also production methods, do actually vary to some extent between the old and new products (KOFA 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations